Freedom of the Press during COVID-19 Pandemic: a Comparative Overview (TEST Trento Student Law Review, 2024)
The emergence of the COVID-19 pandemic hindered the maintenance of stability in many fields, including the working environment of the media sector. Therefore, the UN Human Rights Committee and the Council of Europe issued several guidelines and informative documents to ensure press freedom and the significance of the media's work during the period of the coronavirus crisis. Ac- cordingly, this article applies a comparative analyzing method to ob- serve compliance with international standards in the chosen jurisdic- tions. Firstly, several cases between media workers and governmental agencies in Northern Europe countries are reviewed from the human rights perspective. Subsequently, the governmental bills and amend- ments to Hungarian and Russian laws are commented on through an interpretative lens. Finally, challenges brought by the new standards and regulatory norms are assessed on grounds of the protection of health and public safety.The same approach is followed in Azerbaijan's legal framework, where specific amendments have been introduced to both the Code of Administrative Offenses and the Criminal Code. These amend- ments explicitly prohibit the dissemination of disinformation during emergencies, especially when it poses a real and imminent threat to the life and health of individuals. Furthermore, corresponding legal provisions have been analyzed, outlining sanctions such as admin- istrative imprisonment or deprivation of freedom in the respective codes. In the end, guided by the global standards of international and regional human rights organizations, recommendations are indicated for developing a legal policy against disinformation.
Keywords: State of emergency; Fake news; Dissemination; Legitimate Aim; Proportionality; Transparency